A joint clutter suppression method based on robust principal component analysis and total variation denoising. Issue 5 (12th December 2021) - Xu, Bangzhen; Lu, Xingyu; GU, Hong; Su, Weimin
Abstract: In the scene of ground moving target detection, the target echo information is often corrupted by strong clutter. In this letter, a joint clutter suppression algorithm is proposed based on robust principal component analysis and total variation denoising for pulse Doppler radar. The novel method named total variation‐ robust principal component analysis replaces the l1‐norm in robust principal component analysis algorithm with a total variation seminorm. Total variation robust principal component analysis retains the clutter suppression ability of robust principal component analysis, and effectively separates the target from the noise in range‐Doppler domain.